Prioritizing climate change adaptation needs for food security in 2030 - Lobell, David B; Burke, Marshall B; Tebaldi, Claudia; Mastrandrea, Michael D; Falcon, Walter P; Naylor, Rosamond L (Science (American Association for the Advancement of Science), 2008)
Investments aimed at improving agricultural adaptation to climate change inevitably favor some crops and regions over others. An analysis of climate risks for crops in 12 food-insecure regions was conducted to identify adaptation priorities, based on statistical crop models and climate projections for 2030 from 20 general circulation models. Results indicate South Asia and Southern Africa as two regions that, without sufficient adaptation measures, will likely suffer negative impacts on several crops that are important to large food-insecure human populations. We also find that uncertainties vary widely by crop, and therefore priorities will depend on the risk attitudes of investment institutions.